Planning Management To Improve The Value Of The Lightning Protection Grounding System At The Ccr Building At Sultan Syarif Kasim II International Airport Pekanbaru - Muhammad Caesar Akbar; Tri Dina Agustina Panjaitan (Yayasan Sinergi Multidimensi Kreatif, 2024)
Sultan Syarif Kasim II International Airport Pekanbaru is equipped with an Airfield Lighting System (ALS) just like airports in general. ALS is a visual landing aid that functions to assist and serve aircraft during takeoff, landing and taxiing so that they can move efficiently and safely. The ALS is supplied by CCR (Constant Current Regulator). CCR is a constant current power supply used to supply ALS equipment. The CCR building at Sultan Syarif Kasim II International Airport Pekanbaru is also equipped with a lightning rod with an electrostatic type which is intended to be able to flow lightning currents directly to the ground and not hit the building and not damage the electronic equipment in the CCR building. But in November there was a damage to the CCR module of the PAPI lamp so that the CCR could not operate. This is due to a strong lightning strike that results in a